Utilization of L-cell nucleoside triphosphates by Chlamydia psittaci for ribonucleic acid synthesis. - Hatch, T P (J Bacteriol, 1975)
Long-term, 32-P-labeled L cells were infected with the obligately intracellular parasite Chlamydia psittaci (strain 6 BC). At 20 h postinfection, [3-H]uridine was added, and the infected cells were sampled at intervals for incorporation of the labels into the uridine triphosphate (UTP) and cytidine triphosphate (CTP) pools of the host L cell and the uridine monophosphate (UMP) and cytidine monophosphate (CMP) in 16S ribosomal ribonucleic acid (RNA) of the parasite. The specific activity of the nucleotides was calculated from the ratio of 3-H to 32-P counts in the nucleotides. The rate of approach to equilibrium labeling of UTP and CTP in L-cell pools and UMP and CMP in 16S RNA from the exogenous uridine label was determined from the increase in the ratios of the specific activities of CTP to UTP and CMP to UMP with time. The rate of approach to equilibrium CMP:UMP labeling of the 16S RNA of C. psittaci was consistent with the rate predicted from the kinetics of labeling of the CTP and UTP pools of the host L cell. In analogous experiments, the rate of approach to equilibrium guanosine monophosphate:adenosine monophosphate labeling of 16S RNA from an exogenous [14-C]adenine label was consistent with the rate predicted from the kinetics of labeling of the purine nucleoside triphosphate pool of the host cell. These results support the concept that members of the genus Chlamydia owe their obligate intracellular mode of reproduction to a requirement for energy intermediates which is fulfilled by the host cell. In addition, evidence was obtained that the total acid-soluble purine nucleoside triphosphate pool of L cells accurately represents the precursors of L-cell 18S ribosomal RNA.